2016
DOI: 10.1016/j.appet.2016.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Are food-related perceptions associated with meal portion size decisions? A cross-sectional study

Abstract: The purpose of this study was to test a comprehensive model of meal portion size determinants consisting of sociodemographic, psychological and food-related variables, whilst controlling for hunger and thirst. Using cross-sectional nationally representative data collected in 2075 participants from the Island of Ireland (IoI) and Denmark (DK), eight separate hierarchical multiple regression analyses were conducted to examine the association between food-related variables and meal portion size (i.e. pizza, veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
16
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 38 publications
7
16
1
Order By: Relevance
“…Willingness to report emotional difficulties in men may account for some of this difference [ 41 ], or, alternatively suggest that factors other than emotions play a larger role in binge eating in men. It is unclear why differences between countries emerged, although the pattern is consistent with previous findings that Danish females scored lower on a measure of eating disorder symptoms than indicated in US or international norms [ 42 ], and lower than Irish participants on an emotional eating scale [ 43 ].…”
Section: Discussionsupporting
confidence: 73%
“…Willingness to report emotional difficulties in men may account for some of this difference [ 41 ], or, alternatively suggest that factors other than emotions play a larger role in binge eating in men. It is unclear why differences between countries emerged, although the pattern is consistent with previous findings that Danish females scored lower on a measure of eating disorder symptoms than indicated in US or international norms [ 42 ], and lower than Irish participants on an emotional eating scale [ 43 ].…”
Section: Discussionsupporting
confidence: 73%
“…Current appetite status was measured using a seven-point scale for hunger (1 = not hungry at all, 7 = extremely hungry) and a similar scale for thirst (1 = not thirsty at all, 7 = extremely thirsty). These items were previously used in a portion size selection survey [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similar to a previous portion size selection survey [ 28 ], to measure familiarity with each of the four types of food examined in the survey (cereal, soup, lasagne, yoghurt) respondents were asked how often they eat each food. Respondents selected from one of the following options: “Never”, “Less than once a year”, “Once or twice a year”, “Every few months”, “Once or twice a month”, “Once a week”, “A couple of/few times a week”, and “Daily”.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Personal norms were also larger for foods with a higher liking rating (β = 0.142, p < 0.001) [37]. Other studies have also confirmed that portion size norms are influenced by weight status and gender, as well as socio-demographics, childhood experiences and personal motivational factors including dietary restraint [38][39][40]. Further evidence suggests that individuals perceive a wide range of portion sizes related to a particular food to be the 'norm' , which suggests that significant confusion exist around estimating appropriate portion sizes [23].…”
Section: Appropriateness or Consumption Normsmentioning
confidence: 80%